Obtenção e caracterização de compósitos de benzoxazina/fibra de carbono - Bandeira, Cirlene Fourquet [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
A series of new resins have been developed meeting the needs of an increasingly demanding market, among these the polibenzoxazin resins which constitute a new class of thermoset phenolic resin, which is overcoming the properties of traditional epoxy and phenolic resins when applied in the aerospace industry. With this, the present work aims to synthesize high performance benzoxazine resin called oAI-a (ortho-amide-imide benzoxazin), process composite benzoxazin/carbon fiber via'Hand lay up'using the benzoxazin phenol resins diamino diphenyl methane (P-DDM), the resin oAI-a and the benzoxazine resin commercially available (Epsilon 99100 RTM) via compression hot molding and characterize their physical and chemical properties both under dry conditions and exposed to ultraviolet radiation, humidity and heat and jet fuel, helping it to control production and characterization of new materials with aerospace applications. The results obtained from this study were compared between themselves and with the mechanical and thermal properties of traditional epoxy and phenolic resins available in the literature. The results show that benzoxazine resin composites Epsilon 99100 RTM and P-DDM exhibit good consolidation glass transition temperature around 162°C to the resin Epsilon 99100 RTM and 168°C to the resin P-DDM and good thermal stability. In the case of the composites obtained with Epsilon 99100 RTM resin the conditioning by immersion in water its Tg was reduced 12%, and up to 4.5% for samples UV conditioned when compared to nonconditioned samples. It was also observed that for the samples exposed to aviation kerosene was an increase in the Tg value of up to 3.5% compared with the results obtained in nonconditioned samples. In addition, samples conditioned in water showed an increase of interlaminar shear strength(22%) compared to non-conditioned samples; while the samples immersed in jet fuel showed no significant variation in their performance

Ao encontro das necessidades de um mercado cada vez mais exigente, uma série de novas resinas vem sendo desenvolvidas; dentre estas as resinas polibenzoxazinas, que constituem uma nova classe de resinas fenólicas termorrígidas, que vem superando as propriedades das tradicionais resinas epóxi e fenólica, quando aplicadas na indústria aeroespacial. Com isto, o presente trabalho tem como objetivo sintetizar a resina benzoxazina de alto desempenho denominadas oAI-a (benzoxazina orto-amida-imida), processar compósitos de benzoxazina/fibra de carbono via'Hand lay up', utilizando as resinas benzoxazina fenol-diamino difenil metano (P-DDM), a resina oAI-a e a resina benzoxazina comercialmente disponível (Epsilon 99100 RTM), via moldagem por compressão a quente, e caracterizar suas propriedades físico-químicas, tanto em condições secas como expostas a radiação ultravioleta, umidade e calor e querosene de aviação, dando subsídios para o domínio da produção e caracterização de novos materiais com aplicações aeroespaciais. Os resultados obtidos a partir deste trabalho foram comparados entre si e com as propriedades mecânicas e térmicas das tradicionais resinas epóxi e fenólica disponíveis na literatura. Os resultados mostram que os compósitos de resina benzoxazina Epsilon 99100 RTM e P-DDM apresentam boa consolidação, temperatura de transição vítrea em torno de 162°C, para a resina Epsilon 99100 RTM e 168°C para a resina P-DDM e boa estabilidade térmica. No caso dos compósitos obtidos com a resina Epsilon 99100 RTM, o condicionamento por imersão em água reduziu sua Tg em 12%, e até 4,5% para as amostras condicionadas em UV, quando comparadas com as amostras não condicionadas. Foi também observado que para as amostras expostas ao querosene de aviação houve um aumento do valor da Tg de até 3,5%, quando comparado com os ... (Resumo completo, clicar acesso eletronico abaixo)
Obtainment and preparation of carbon fiber/benzoxazine composite
Keywords: Materiais compostos; Compositos polimericos; Cisalhamento; Fibras de carbono; Compostos fibrosos; Resinas compostas; Analise termica; Composite materials